THU0597 CORNEAL MELT - DON'T ALWAYS BLAME RHEUMATOID ARTHRITIS. (2nd June 2020) - Munir, A.; Sheehy, C.
Abstract : Background: Corneal melt is a rare inflammatory disease of the peripheral cornea; it may lead to perforation of the globe and visual failure. Corneal melt can be a manifestation of systemic vasculitis in patients with RA and other conditions, such as cancer. Without early and aggressive treatment it may be associated with a poor visual outcome and a high mortality. It has been reported in patients with stable RA. Objectives: A case report in a patient with long standing but well controlled Rheumatoid Arthritis (RA) and metastatic disease. Methods: A 75 year old male with a background of sero positive Rheumatoid Arthritis for more than 10 years presented to the Eye Casualty with a two week history of a painful left red eye. His other medical history was significant for Stage IIB poorly differentiated cancer of the left lower lobe. Left lower lobectomy with a patch of diaphragm resected. Intratumoural lymphovascular invasion noted. He completed Adjuvant Carboplatin/Vinorelbine chemotherapy September, 2017. He had DVT proximal left leg 22 nd of September, 2017. Follow up CT in 2018 demonstrated a right renal upper pole lesion for which he was awaiting biopsy with?metastatic lung disease vs primary renal carcinoma. His RA was well controlled on Methotrexate 10mg weekly. He had been treated by the ophthalmology team for left marginal Keratitis for the prior 2 months with steroid eye drops without significant improvement. On presentation to ED, he described sharp eye pain, waking him from the sleep, associated with watery discharge and photophobia. Examination showed corneal melt in left eye involving 25% of inferior portion of the cornea and spastic entropion with injecting eye lashes. He had no active joints and there were no other signs of vasculitis. CRP was 4.1. He had a negative ANA and ANCA; viral swabs were negative. He was admitted under the medical team. Intravenous Methyl Prednisolone was started. The patient felt better after 5 days of Methyl Prednisolone. Left temporary tarsorrhaphy was done by Ophthalmology. Cyclophosphamide was initiated after discussion with Oncologist pending the result of the renal biopsy. Patient was discharged after 5 days of admission in the hospital Results: The renal biopsy was positive for metastatic Squamous cell carcinoma of lung. Cyclophosphamide was withdrawn and he was started on Carboplatin/Gemcitabine. The corneal melt improved with complete resolution of his visual symptoms. Conclusion: In this case, although the history of RA was felt by the ophthalmology team to be the most likely association with the corneal melt, we would argue the oncological diagnoses were likely the driving force behind the presentation. References: [1] Sule A, Balakrishnan C, Gaitonde S, Mittal G, Pathan E, Gokhale NS, et al. Rheumatoid corneal melt. Rheumatology (Oxford)2002;41:705–6. [2]S. Yano, K. Kondo, M. Yamaguchi et al., "Distribution and function of EGFR in human tissue and the effect of EGFR tyrosine kinase inhibition, " Anticancer Research, vol. 23, no. 5, pp. 3639–3650, 2003. Disclosure of Interests: None declared